The relationship between lean and performance measurement in service and manufacturing organisations in New Zealand : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Accounting at Massey University, Manawatū, New Zealand - Roos, Christina Maria (Massey University, 2024)
This thesis examines the relationship between lean and performance measurement systems (PMSs) in New Zealand private and public organisations. There is a dearth of research on lean and PMSs, despite the importance of understanding this relationship. To provide insights and an understanding of this relationship, this study identifies and examines lean techniques and the corresponding performance measures applied to measure lean performance. The research data were analysed using Searcy’s (2004) framework of lean performance dimensions and the findings were informed by contingency theory. The research conclusions were drawn from qualitative interpretations of the data through thematic analysis. The research findings show that lean is still in an emergent state in New Zealand and that managers associate lean with reducing waste to reduce costs, promote continuous improvement, improve quality, and deliver customer value. This differs from the global perspective of providing customer value through continuous improvement (Thornton et al., 2019; Albzeirat et al., 2018). The lean techniques implemented by the lean organisations reflect the managers’ association of lean with reducing cost and promoting continuous improvement, with a marginal focus on improving customer value. Organisations that successfully use lean techniques remain in a ‘black hole’ between measuring lean performance and the inclusion of lean performance dimensions in the PMS. Less than half of the organisations adapted their PMSs to include lean performance, nor did they implement specific lean KPIs to measure and evaluate lean performance. In those organisations where managers had identified, implemented, and used critical lean success factors, they had concurrently modified their PMS to include lean KPIs. Nonetheless, dollars saved are still recognised as the most important lean contribution, subsequently, once dollar-related goals were reached, organisations restored their traditional PMSs. As such, lean performance was neglected, and the existing lean practices were not associated with PMS. Ultimately, most organisations did not adapt their PMSs sufficiently to accommodate lean, and consequently, the organisations’ PMSs did not adequately capture lean outcomes. The implications for organisations and CEOs are that they need to shift focus from cost savings and profits to lean techniques and map the correct key performance indicators to the PMS to fully measure and evaluate lean outcomes.
Figures are reused with permission.
Keywords: Organizational effectiveness; Measurement; Performance standards; Management; Business logistics; Evaluation; Total quality management; New Zealand; performance measurement systems; contingency theory; lean performance dimensions; 350711 Organisational planning and management